The choroid plexus-cerebrospinal fluid interface in Alzheimer′s disease: more than just a barrier - Sriram Balusu; Marjana Brkic; Claude Libert; Roosmarijn E Vandenbroucke (Neural Regeneration Research, 2016)
The choroid plexus is a complex structure which hangs inside the ventricles of the brain and consists mainly of choroid plexus epithelial (CPE) cells surrounding fenestrated capillaries. These CPE cells not only form an anatomical barrier, called the blood-cerebrospinal fluid barrier (BCSFB), but also present an active interface between blood and cerebrospinal fluid (CSF). CPE cells perform indispensable functions for the development, maintenance and functioning of the brain. Indeed, the primary role of the choroid plexus in the brain is to maintain homeostasis by secreting CSF which contains different molecules, such as nutrients, neurotrophins, and growth factors, as well as by clearing toxic and undesirable molecules from CSF. The choroid plexus also acts as a selective entry gate for leukocytes into the brain. Recent findings have revealed distinct changes in CPE cells that are associated with aging and Alzheimer′s disease. In this review, we review some recent findings that highlight the importance of the CPE-CSF system in Alzheimer′s disease and we summarize the recent advances in the regeneration of brain tissue through use of CPE cells as a new therapeutic strategy.